Evaluation of discharge equations of the piano key weirs. (August 2019) - Kumar, Binit; Kadia, Subhojit; Ahmad, Zulfequar
Abstract: In present scenario, Piano key weir has played a vital role in increasing the discharge capacity of the available dams. This modified weir is the replacement of creaky and conventional labyrinth weir and it is best suited for the low head dams. This new labyrinth type weir is utmost solution for the rehabilitation of the spillways all across the globe. There are various equations available for the estimation of coefficient of discharge of Piano key weir. The present study encapsulates about the observable fact of coefficient of discharge for the Piano key weir and assigns different procedure for its evaluation. The validation of the four existing equations given by the investigators for the coefficient of discharge is monitored in the study. The graphical representation and statistical perusal of the equations given by the investigators show that the relationship proposed by Crookston et al.; Cicero and Delisle predict coefficient of discharge better than other equations for the data sets used in this present study. For these two equations 97% results lie within ±20% error lines. The present experimental study is also compared with the relationships given by the previous investigators. The equation suggested by Crookston et al. estimates coefficient of discharge effectively for all ranges of H/P, whereas the equation proposed by Cicero and Delisle is slightly more efficient for H/P between 0.2 and 0.8. Highlights: Graphically, Crookston et al. (2018) and Cicero and Delisle (2013) equations show better results among all four equations. Statistical parameters also depict better performance of the above two equations. For head to weir height ratio 0.2 to 0.8, the equation given by Cicero and Delisle (2013) is slightly more efficient.